Bronchopulmonary dysplasia: Clinical perspective. Issue 3 (27th February 2014) - Jain, Deepak; Bancalari, Eduardo
<x xml:space="preserve">Abstract</x> Since Northway's original description of BPD almost 45 years ago, the clinical presentation of BPD has evolved into a disease process, which mostly involves extremely premature infants. This new form of BPD is the result of multiple antenatal and postnatal factors that can cause injury to the developing lung leading to altered alveolar and vascular development. Over the years, there has been considerable increase in knowledge of factors that contribute to the development of BPD. This has led to different strategies for prevention as well as management of BPD. Some of these strategies have been successful and have withstood the test of clinical trials, such as vitamin A supplementation, post‐natal steroids, caffeine, and volume targeted ventilation. The evidence for other interventions has been weak or negative. With better understanding of the complex and multifactorial pathogenesis of BPD, it is quite clear that any single therapy is very unlikely to eliminate this problem unless it reduces prematurity. Further development in prevention and treatment of BPD will likely need a multi‐pronged strategy with novel therapeutic agents acting at various stages of the disease process. Birth Defects Research (Part A) 100:134–144, 2014. © 2014 Wiley Periodicals, Inc.